Dockless bike-sharing system: Solving the problem of faulty bikes with simultaneous rebalancing operation - Muhammad Usama; Onaira Zahoor; Yongjun Shen; Qiong Bao (Journal of Transport and Land Use)
The Free-Floating Bike-Sharing System (FFBS) enables commuters to pick up and drop off a shared bike without going to a docking station before and after the trip. However, the specific sharing features of the FFBS can also be a problem for users because randomly scattered and faulty bikes within the system can result in bike unavailability and maintenance difficulties. This not only negatively impacts the company’s service quality but also causes user safety issues. In this study, a mechanism for the rebalancing of useable bikes and faulty bikes is presented in two steps: 1) gathering each faulty bike at a station determined by the model traversing the shortest path by light service vehicles; and 2) enabling the rebalancing operation to obtain optimal bike inventory levels at all stations and collect faulty bikes at a depot. The destination station from which each faulty bike is taken is considered a decision variable rather than shifting them to a closer station. The mechanism is based on minimizing the total cost of the rebalancing operation by optimizing the formulated problem, supported by time and capacity constraints. Using CPLEX solver, the validity of the model is tested through different numerical experiments.